Attention Bias Test Differentiates Anxiety and Depression in Sheep - Monk, Jessica E.; Belson, Sue; Colditz, Ian G.; Lee, Caroline (Frontiers in Behavioral Neuroscience, 2018)
Negative affective states such as anxiety and depression pose a risk to animal welfare, however practical tests for assessing these states in animals are limited. In humans, anxious individuals are shown to pay more attention towards threatening information than non-anxious individuals, known as an attention bias. Previously, an attention bias test was developed and validated as a measure of anxious states in sheep, where more anxious sheep showed increased attention towards a threat (dog) and were more vigilant than Control animals. Studies in humans suggest that attention biases also occur in depressed individuals, with observations of attention biases towards threats, as well as biases away from positive stimuli. Given these findings, we hypothesised that an attention bias test for sheep could also be used to assess states of depression. We predicted that Merino ewes in pharmacologically induced Depressed (para-chlorophenylalanine) and Anxious (m-chlorophenylpiperazine) states would show greater attention towards a threat than Control animals (saline), but that the Depressed sheep would show relatively less interest in a positive stimulus (photograph of a conspecific). During testing, Depressed sheep paid more attention towards the threat and less towards the photograph than Control animals as predicted (Analyses of Variance, P<0.05, n=20 per treatment). Interestingly, anxious sheep showed an attention bias in the opposite direction, paying more attention towards the photograph and less towards the threat than Control animals (P<0.05). Both Anxious and Depressed sheep were more vigilant than Control animals (P=0.002). These results suggest the attention bias test can be used to measure and differentiate states of depression and anxiety in livestock. The bidirectional nature of the attention bias identified between treatments highlights the importance of measuring multiple behaviors in the test and considering the context in which the test is applied. This will enable a clearer characterization of the affective state of an animal, as an aspect of its welfare.